2020
DOI: 10.3390/clockssleep2040031
|View full text |Cite
|
Sign up to set email alerts
|

Alarm Tones, Voice Warnings, and Musical Treatments: A Systematic Review of Auditory Countermeasures for Sleep Inertia in Abrupt and Casual Awakenings

Abstract: Sleep inertia is a measurable decline in cognition some people experience upon and following awakening. However, a systematic review of the current up to date evidence of audio as a countermeasure has yet to be reported. Thus, to amend this gap in knowledge, the authors conducted this systematic review beginning with searches in three primary databases for studies published between the inception date of each journal and the year 2020. Search terms contained “Sleep Inertia” paired with: “Sound”; “Noise”; “Music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
(266 reference statements)
1
4
0
Order By: Relevance
“…A recent study that evaluated sound options for residential fire alarms found that low-frequency tones, the voice of a female stranger, and the voice of the child's mother were significantly more effective at waking children than high-frequency tones [14]. This is consistent with the findings of a systemic review on the effectiveness of different alarm types on sleep inertia [15]. Based on our findings and prior evidence, bedwetting alarms require more alarm tone and volume options, and it is recommended that device developers ensure that low-frequency and voice tones are incorporated to maximize their effectiveness.…”
Section: Principal Findingssupporting
confidence: 74%
“…A recent study that evaluated sound options for residential fire alarms found that low-frequency tones, the voice of a female stranger, and the voice of the child's mother were significantly more effective at waking children than high-frequency tones [14]. This is consistent with the findings of a systemic review on the effectiveness of different alarm types on sleep inertia [15]. Based on our findings and prior evidence, bedwetting alarms require more alarm tone and volume options, and it is recommended that device developers ensure that low-frequency and voice tones are incorporated to maximize their effectiveness.…”
Section: Principal Findingssupporting
confidence: 74%
“…Various studies aimed to determine how to escape sleep inertia quickly and effectively [36]. For example, McFarlane et al [37][38][39] explored auditory factors, such as alarm sounds, to decrease the influence of sleep inertia, and Hilditch et al [40] attempted to induce arousal using light of specific frequencies. Additionally, physical activity has been addressed as the primary countermeasure to sleep inertia.…”
Section: Introductionmentioning
confidence: 99%
“…While potential countermeasures have been evaluated as options, more research is needed. These reactive countermeasures include but are not limited to: a) bright light 35) ; b) caffeinated gum 36) ; c) sound 37) ; and d) exercise 38,39) . For example, in a proof-of-concept study by Kovac, Vincent 40) , exercise completed immediately upon waking during the night increased noradrenaline levels and reduced sleepiness levels after 5 minutes 40) .…”
Section: On-call Work and Sleep 6 A) The Efficacy Of Existing Countermeasuresmentioning
confidence: 99%
“…While potential countermeasures have been evaluated as options, more research is needed. These reactive countermeasures include but are not limited to: a) bright light 35 ) ; b) caffeinated gum 36 ) ; c) sound 37 ) ; and d) exercise 38 , 39 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation